The Use of an Expendable Mold Casting Technique for Semi-solid Formable Feedstock Production: The Combination of Lost Foam and Cooling Slope Casting - Tütük, İbrahim; Acar, Serhat; Güler, Kerem Altuğ (Springer, 2025)
This study investigates expendable mold casting as an innovative approach to producing semi-solid formable aluminum feedstock by integrating the lost foam casting (LFC) technique with the cooling slope method to generate semi-solid slurry. Silica and chromite sands were employed as mold materials, and expanded polystyrene (EPS) patterns were prepared both with and without refractory coatings. The effects of sand type, pattern coating, and cooling slope application on the microstructural and mechanical properties of A356 alloy were systematically evaluated in both as-cast and reheated conditions. The finest and most spheroidal microstructures were achieved using a combination of chromite sand, uncoated patterns, and cooling slopes. After reheating, the smallest average grain size (77.1 lm) and highest shape factor (0.93) were observed. Significant improvements in grain refinement during solidification and enhanced sphericity following reheating were demonstrated. Moreover, hardness values were maintained or slightly improved in samples with finer microstructures despite the expected grain coarsening after reheating. Compared to conventional permanent mold casting methods, the proposed hybrid technique offers superior control of thermal gradients and solidification dynamics, resulting in more uniform and spheroidal grains and, consequently, enhanced semi-solid formability.
Keywords: Semi-Solid Forming; Lost Foam Casting; A356